STRES BERHUBUNGAN DENGAN KUALITAS TIDUR MAHASISWA KEPERAWATAN TINGKAT AKHIR - Riyadi, Muskhab Eko; Ahmad, Siti Nurjana (Jurnal Pendidikan Kesehatan (e-Journal), 2024)
A study of 200,000 students at more than 400 universities stated that the incidence of academic stress among students is greater than before. Stress is often experienced by final-year students due to the many demands in the academic field. This accumulated stress makes students more susceptible to experiencing sleep disorders. The research aimed to determine the relationship between stress levels and sleep quality in final-year nursing students at STIKes Surya Global Yogyakarta. This is a quantitative study with a cross-sectional design, the population in this study was 140 final-year nursing students who were working on their thesis at STIKes Surya Global Yogyakarta. Based on calculations, the minimum sample size was 59 respondents. The sampling technique uses a random sampling proportion technique. The instruments in this research were the Perceived Stress Scale (PSS) to measure stress levels and the Pittsburgh Sleep Quality Index (PSQI) to determine the quality of respondents' sleep. Statistical tests use the Kendal-Tau test. The research results showed that the majority of final year nursing students at STIKes Surya Global Yogyakarta experienced moderate stress, namely 33 respondents (55.9%) and had poor sleep quality, namely 54 respondents (91.5%). Statistical tests show a p-value of 0.000 and a correlation coefficient of 0.471. The conclusion is that there is a strong relationship between stress and sleep quality in final-year students at STIKes Surya Global Yogyakarta.